PERTUMBUHAN OKULASI TANAMAN KARET (Hevea brassiliensis Muell arg.) DENGAN TINGGI PENYERONGAN BATANG BAWAH DAN BENZILAMINOPURIN (BAP) PADA PEMBIBITAN POLIBEG - Bayu Pratomo; Chairani Hanum; Lollie Agustina P Putri (Talenta Publisher, 2016)
The growth of the rubber depends on some factors in the nursery. One of critical point was on stumping fase. After stumping fase, the number of death plants is quite high at young budding of seedling. This research used Factorial Radomized Complete Block Design (RCBD) with two factors and three replications. The Height of rootstock stumped (10, 20 and 30 cm) and the concentration of BAP (15, 30, 45 and 60 mg / 200 g Lanolin). Results of the research showed the number of life budding shoots significantly affect the interaction of stumping and BAP. The results showed that rootstock stumped 30 cm and BAP 60 g / 200 g Lanolin is the best treatment for height of budding shoots (410.67 mm) and the percentage of life budding shoots (66.67%).